2007
DOI: 10.1128/iai.00922-07
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host Innate Immune Response in the Bladder by UropathogenicEscherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC), the most frequent cause of urinary tract infection (UTI), is associated with an inflammatory response which includes the induction of cytokine/chemokine secretion by urothelial cells and neutrophil recruitment to the bladder. Recent studies indicate, however, that UPEC can evade the early activation of urothelial innate immune response in vitro. In this study, we report that infection with the prototypic UPEC strain NU14 suppresses tumor necrosis factor alpha (TNF-␣)-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
91
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 44 publications
13
91
1
2
Order By: Relevance
“…Several studies reported suppression of cytokine production in response to UPEC in vitro infection. 35,64,65 This discrepancy with our results is likely due to differences in post-infection incubation time and is therefore reflecting differences between acute and persistent phase of infection.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies reported suppression of cytokine production in response to UPEC in vitro infection. 35,64,65 This discrepancy with our results is likely due to differences in post-infection incubation time and is therefore reflecting differences between acute and persistent phase of infection.…”
Section: Discussioncontrasting
confidence: 57%
“…The persistence of a 1-2 E. coli clones in the neurogenic bladder may be due to E. coli's growth rate in the urine over other species 18 and/or its ability to evade the host's innate immune response. 19 In addition, phylogenetic group and/or virulence genes may promote selection and persistence of specific clones.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of an infection, UPEC can stimulate a number of antimicrobial, proinflammatory, prodifferentiation, proliferation, and host cell death pathways (Mulvey, 2002;Mysorekar et al, 2002). In some cases, UPEC can reportedly modulate these signaling events, causing attenuation of host inflammatory responses and potentiating host apoptotic cascades (Klumpp et al, 2001(Klumpp et al, , 2006Hunstad et al, 2005;Billips et al, 2007). These phenomena have been linked in part to the suppression of nuclear factor-B (NF B) activation and downstream signaling by unknown factors associated with UPEC (Klumpp et al, 2001;Hunstad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%